(untitled) (Annals of Medical Research, 2022)
Aim: Neisseria meningitidis is the cause of sepsis and meningitis with high mortality and morbidity. Vaccination is the most effectiveway to prevent infectious diseases. There are 4 different meningococcal vaccines that can be applied in our country and these vaccines are not yet available in routine vaccination program. It was aimed to determine the knowledge level of parents with children under 5 years of age about invasive meningococcal disease and their attitudes towards the administration of meningococcal vaccines, which are not included in the routine immunization program, to their children. Materials and Methods: A questionnaire consisting of 17 questions was applied to parents of children under the age of 5, who applying to pediatric outpatient clinics for any reason. Nine of the questionnaire questions were about sociodemographic characteristics, routine control and vaccination. The remaining 7 questions were about meningococcal infection, transmission routes and vaccines. Results: A survey was conducted with a total of 224 parents, 142 (63.3%) female and 82 (36.7%) male. Two hundred-two of the parents (90.1%) stated that they had all routine vaccinations on time for their children. Eighteen parents (8%), could not have all vaccines on time due to pandemic and health problems. Sixty-two (27.6%) parents reported that they knew about meningococcal disease. Only 56 (25%) of the parents stated that they knew at least one meningococcal vaccine. After brief information about meningococcal infection and vaccines, 114 parents (50.8%) stated that they wanted their children to be vaccinated. Conclusion: When parents are informed about the meningococcal disease and its severity and then recommended vaccination, the vaccination rate will increase significantly. It is important for healthcare professionals to be more aware of this issue and to inform families.